THE INFLUENCE OF OPENNESS TO EXPERIENCE, CONSCIENTIOUSNESS, ECTROVERSION, AGREEABLENESS, AND NEUROTICISM AN CELLULAR SERVICE CUSTOMER LOYALTY IN PEOPLE IN LHOKSEUMAWE CITY - Farah Aidilla; Sapna Biby; Mariyudi; Heriyana (PT. Radja Intercontinental Publishing, 2024)
The aim of this research is to determine the influence of openness to experience, conscientiousness, extroversion, agreeableness and neuroticism on the loyalty of cellular service customers in the community in Lhokseumawe City. The research method is a quantitative research method. This research was conducted by Lhokseumawe City. The population in this study is the people of Lhokseumawe City who use XL Axiata, the sample in this study was 96 respondents. The research results show that customer openness (X1), conscientiousness (X2), ecrtoversion (X3), and agreeableness (X4) partially have a positive and significant effect on customer loyalty (Y) of cellular services in the community in Lhokseumawe City. Meanwhile, neuroticism (X5) has a negative and significant effect on customer loyalty (Y) for cellular services in the community in Lhokseumawe City. Simultaneously, openness to experience, conscientiousness, extroversion, agreeableness and neuroticism influence customer loyalty in cellular services in Lhokseumawe City, this is because based on the F test, the significance value is found to be 0.000 < 0.05, then Fcount is 13.371 > Ftable 3.13